Delovanje šolskih sester kongregacije sv. Frančiška Asiškega - Kristusa Kralja v ZDA med letoma 1909 in 1915 - Friš, Darko (Dve domovini, 1992)
The second half of the 19th century saw a more massive influx of Slovene immigrants into the U.S. The Catholics to America, too, and continued its work there by establishing Slovene parishes. The great majority of Slovene immigrants wanted for their children to preserve their religion and their mother tongue. The biggest problem was the shortage of qualified teaching staff. In that respect were similarities between Slovene and Croatian schools.
Keywords: 1909/1915; Catholic Church; katoliška cerkev; slovenski izseljenci; United States of America; ZDA; župnije